Memórias resistentes nos quintais quilombolas de Pilar do Sul (SP) - Paixão, Gabriella Marques Leite (Universidade Federal de São Carlos, 2018)
Quilombola communities have a long history of sustained resistance since slavery. Their traditions were oppressed and adapted to the reality they were forced to adopt, learning to relate to nature to survive, linking the memories of the representations of their identity to the new territory. In Pilar do Sul (SP), the quilombola community Fazenda Pilar claims the titling of their lands for the resumption of traditional subsistence practices. Approximately 70% of this territory has been urbanized, remaining only to the homegardens of their houses, reminiscences of relationship with nature. The participant research described here, sought to verify and describe if the traditional knowledge of quilombolas from Pilar do Sul are present in their homegardens. To this end, thematic interviews were conducted with quilombolas to record oral history. The results show that backyards preserve knowledge passed down through the generations, even if they are redefined, tainted or hidden.
Memories resistent in quilombolas’ homegardens of Pilar do Sul (SP)
Keywords: Memória; Quintais; Quilombolas; Pilar do Sul; Memory; Homegardens; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA DAS POPULACOES AFRO-BRASILEIRAS; CIENCIAS BIOLOGICAS; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA POLITICA; CIENCIAS HUMANAS::HISTORIA::HISTORIA DO BRASIL::HISTORIA REGIONAL DO BRASIL